2005
DOI: 10.1007/s11251-004-2322-4
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic and social scripts in computer?supported collaborative learning

Abstract: Collaborative learning in computer-supported learning environments typically means that learners work on tasks together, discussing their individual perspectives via text-based media or videoconferencing, and consequently acquire knowledge. Collaborative learning, however, is often sub-optimal with respect to how learners work on the concepts that are supposed to be learned and how learners interact with each other. Therefore, instructional support needs to be implemented into computer-supported collaborative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
199
1
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 330 publications
(234 citation statements)
references
References 28 publications
9
199
1
9
Order By: Relevance
“…The following example of a discussion, which was supported by a specific computersupported cooperation script (see Weinberger, Ertl, Fischer, & Mandl, 2005) illustrates how knowledge is shared in asynchronous CSCL and coded by us (see Weinberger & Fischer, 2006 for coding rules; original discussion was in German). The discussion is about a specific problem case about a pupil who suffers from suboptimal attribution patterns of himself and his parents.…”
Section: Appendix A: Example Of Analysis Of a Scripted Discourse Excerptmentioning
confidence: 99%
See 1 more Smart Citation
“…The following example of a discussion, which was supported by a specific computersupported cooperation script (see Weinberger, Ertl, Fischer, & Mandl, 2005) illustrates how knowledge is shared in asynchronous CSCL and coded by us (see Weinberger & Fischer, 2006 for coding rules; original discussion was in German). The discussion is about a specific problem case about a pupil who suffers from suboptimal attribution patterns of himself and his parents.…”
Section: Appendix A: Example Of Analysis Of a Scripted Discourse Excerptmentioning
confidence: 99%
“…Table A1 presents a glossary of abbreviations and the overall outcomes of the discourse example in term of the knowledge level approach. ********************** Insert Table A1 about here ********************** The first message is sent by Lena at 10:12 am, enacting the role of case analyst as suggested by the script (see Weinberger et al, 2005). Overall, the Lena-Anna-dyad does not attain a high value in knowledge contribution equivalence, since Lena constructs more adequate concept-case relations in her role as a case Knowledge Convergence 30 analyst than Anna in her role as a constructive critic.…”
Section: Appendix A: Example Of Analysis Of a Scripted Discourse Excerptmentioning
confidence: 99%
“…Of the four studies analyzed, three studies suggested that the existence of scaffolding to assist communication between groups that learn online does not have a direct significant enhancement over learning outcomes (Hron et al 2000;Choi et al, 2005;Ryan 2007). However, the study by Weinberger et al (2005) suggested the opposite.…”
Section: Scaffolding For Online Learningmentioning
confidence: 96%
“…On the other hand, Weinberger et al (2005) conducted a study which revealed positive results for learners who were provided with scaffolding. The authors developed two kinds of scaffolding: (1) social scaffolding organized in such a way that students communicate among each other via techniques like information gathering through asking crucial questions and (2) epistemic scripts that stated the manner in which learners should advance in an allocated assignment and assisted learners to address specific issues.…”
Section: Scaffolding For Online Learningmentioning
confidence: 99%
See 1 more Smart Citation